NURSES CARING FOR LESBIANS. - Farias, Gesiany Miranda; de Azevedo Lima, Vera Lúcia; da Silva, Andrey Ferreira; de Vasconcelos Chaves, Alessandra Carla Santos; Gomes, Valquíria Rodrigues; Silva, Adria Vanessa da; Paixão, Victor Assis Pereira (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2018)
Objective: to identify how nursing care is addressed to lesbians. Method: this is an integrative review study, in the LILACS, PUBMED / MEDLINE and BDENF databases, in publications between 2013 and 2017, using the descriptors lesbian, women's health and nursing care, and presented in the text in the form of figures. Results: 790 articles were publications that did not agree with the pre-established timeline; 68 did not have the summary available for the initial consultation; 39 were revisions; 19, reflections; 793 did not mention nursing care for lesbians in the initial reading of their abstracts, and seven were duplicate articles, resulting in ten studies. Conclusion: the need for further studies involving lesbian sexual orientation and nursing care in Brazil was identified as a priority, as well as showing that many nurses provide care to women based on the mistaken idea that all are heterosexual and, they do not provide effective care because they do not provide guidance on key health care.